High Levels of IgE in Apparently Normal Venezuelan Populations - Merino, Fernando; Arends, Tulio (Investigación Clínica, 2009)
Levels of IgE for Venezuelan normal subjects were determined in 25 blood donors residing in Caracas, 12 donors from a northwestern city (Coro), and 12 apparently healthy subjects from a rural population near Caracas (Tapipa) with African background. Results obtained indicate levels of IgE (Tapipa > Coro > Caracas) higher than European and U.S. population. Even though these results are preliminary because of the smallness of the sample, correlation with the degree of development of these populations, and possibly with the frequency of intestinal parasitosis and eosinophilia, seems to be operating.